Uptake and determinants of immediate and extended postpartum long-acting reversible contraceptive use in Eastern and Western Africa: A systematic review and meta-analysis - Ritbano Ahmed Abdo; Endalew Gemechu Sendo; Erdaw Tachbele Betre; Kedir Hussen (PLoS ONE, 2026)
Background Reducing unintended pregnancies and improving maternal/child health relies heavily on postpartum family planning (PPFP). Despite their high effectiveness, the use of long-acting reversible contraceptives (LARC), such as intrauterine contraceptive device (IUCD) and implants, is inconsistent in Africa after childbirth. This systematic review and meta-analysis aimed to assess the prevalence and determinants of immediate and extended postpartum use of long-acting reversible contraceptives in Eastern and Western Africa. Methods We searched PubMed, the Cochrane Library, Hinari, and gray literature sources (Google Scholar) for studies published between January 1, 2015, and December 12, 2025. Eligible studies reported LARC uptake within 12 months of postpartum. Heterogeneity was assessed using the I² statistic, publication bias using Egger’s test, and study quality using the JBI 2020 checklist. Data were analyzed using Stata version 17 and R version 4.5. Results Sixty-eight studies were included, most of which were from Eastern Africa. The pooled prevalence was 21.7% for immediate postpartum LARC (IPP-LARC) and 19.5% for extended postpartum LARC (EPP-LARC). Uptake was significantly associated with counseling during maternal and child health visits, partner involvement, prior family planning use, and good knowledge. Age ≥ 35 years and higher education level also favored immediate postpartum IUD use. Conclusion The uptake of postpartum LARCs remains low in Eastern and Western Africa. Strengthening FP counseling during MCH services, encouraging partner involvement, and improving knowledge are critical strategies to increase coverage and reduce unmet needs. Trial registration PROSPERO International Prospective Register of Systematic Reviews (ID: CRD420250577642).